Relative Performance Compensation, Contests, and Dynamic Incentives - Casas-Arce, Pablo; Martínez-Jerez, F. Asís (Management Science, 2009)
Contests (or tournaments) are pervasive in organizations. They help performance evaluation by eliminating common shocks affecting agents' performance. However, tournaments are less effective when participants have heterogeneous ability because participants may conclude that the ability gap is too large to be overcome by their effort. Our theoretical analysis shows that a similar loss of motivation arises when tournaments take place over multiple periods because interim performance acts in a way that is similar to heterogeneous ability. Analyzing the sales contests organized by a commodities company, we document that winning participants decrease their effort as their lead extends, whereas the effort of trailing participants fades only when the gap to a winning position is very large. We also show that, on average, when contests are introduced they induce a higher level of effort among participants, although the incentives weaken as the number of participants increases. Finally, we demonstrate that although retailers respond to the multiple performance dimensions of the incentive program in part by shifting effort toward sales of more expensive products, they channel most of the increased effort toward reaching more customers.